The study on the Willingness to pay for conserving historical site of domestic tourists: A case study on historical site of Hueanchan in Luang Prabang City, Lao PDR - PHOTHITAY, Anousith; HOONGSANGPHA, Soudthida; SENGCHANH, Souksamone; PHONGSAVATH, Phetdamone; PHANLA, Phone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Tourism is considered as a key for driving socio-economy for Luang Prabang, tourism is very important potential for tourism development. Tourism resources are categorized in to three elements, including historical, natural and cultural tourism resources, and this study aims to focus for economic value of some selected historical site in Luang Prabang city. This study focuses on two objectives (1) tourism income from selected historical sites in urban Luang Prabang and ( 2 ) willingness to pay for domestic tourists on preserving Huan Chan historical site. Secondary data and questionnaires were used for data collection from 330 domestic tourists in Luang Prabang. The finding for objective 1, shows that Vat Thamphousi historical site generated highest income from 2015-2019, the second larger income is Luang Prabang museum (former royal palace), and the third is UXO visitor center and the least is Huean Chan historical heritage house. However, Huenchan is newly operated for tourism since 2019 and it has a great potential various tourism activity for living culture and sustainable cultural heritage. The second objective results that the price of the respondents are willing to pay for preserving heritage house of Huenchan is 6,250 Lak, and the current price for entrance fee is 10,000 Lak, it is 4,000 Lak lower than the current price. It seems that the economic value of heritage house is not much. However, it is important to operate creative activities for building awareness for young generation to experience and understand the value of their heritage in both material and non-material cultural heritage and it is also very important to generate income regularly for entrepreneurs, employment and for sustainable management of the heritage property.